They see us as less than human Metadehumanization predicts intergroup conflict via reciprocal dehumanization. [article]. - Kteily, Nour
Although the act of dehumanizing an outgroup is a pervasive and potent intergroup process that drives discrimination and conflict, no formal research has examined the consequences of being dehumanized by an outgroup-that is, "metadehumanization." Across 10 studies (N = 3,440) involving several real-world conflicts spanning 3 continents, we provide the first empirical evidence that metadehumanization (a) plays a central role in outgroup aggression that is (b) mediated by outgroup dehumanization, and (c) distinct from metaprejudice. Studies 1a and 1b demonstrate experimentally that Americans who learn that Arabs (Study 1a) or Muslims (Study 1b) blatantly dehumanize Americans are more likely to dehumanize that outgroup in return; by contrast, experimentally increasing outgroup dehumanization did not increase metadehumanization (Study 1c). Using correlational data, Study 2 documents indirect effects of metadehumanization on Americans' support for aggressive policies toward Arabs (e.g., torture) via Arab dehumanization. In the context of Hungarians and ethnic minority Roma, Study 3 shows that the pathway for Hungarians from metadehumanization to aggression through outgroup dehumanization holds controlling for outgroup prejudice. Study 4 examines Israelis' metaperceptions with respect to Palestinians, showing that: (a) feeling dehumanized (i.e., metadehumanization) is distinct from feeling disliked (i.e., metaprejudice), and (b) metadehumanization uniquely influences aggression through outgroup dehumanization, controlling for metaprejudice. Studies 5a and 5b explore Americans' metaperceptions regarding ISIS and Iran. We document a dehumanization-specific pathway from metadehumanization to aggressive attitudes and behavior that is distinct from the path from metaprejudice through prejudice to aggression. In Study 6, American participants learning that Muslims humanize Americans (i.e., metahumanization) humanize Muslims in turn. Finally, Study 7 experimentally contrasts metadehumanization and metahumanization primes, and shows that resulting differences in outgroup dehumanization are mediated by (a) perceived identity threat, and (b) a general desire to reciprocate the outgroup's perceptions of the ingroup. In summary, our research outlines how and why metadehumanization contributes to cycles of ongoing violence and animosity, providing direction for future research and policy. -- (from the authors)